2005
DOI: 10.1042/cs20040220
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygosity for mutations Asp611→Tyr in KCNQ1 and Asp609→Gly in KCNH2 associated with severe long QT syndrome

Abstract: LQTS (long QT syndrome) is an inherited cardiac disorder characterized by prolongation of QT interval, torsades de pointes and sudden death. We have identified two heterozygous missense mutations in the KCNQ1 and KCNH2 (also known as HERG) genes [Asp611-->Tyr (D611Y) in KCNQ1 and Asp609-->Gly (D609G) in KCNH2] in a 2-year-old boy with LQTS. The aim of the present study was to characterize the contributions of the mutations in the KCNQ1 and KCNH2 genes relative to the clinical manifestations and electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Mutations in various genes encoding cardiac ion channels and membrane adaptor proteins are known to cause this syndrome [2], and many LQTS mutations have been identified [3][4][5][6]. A previous study [7] has shown that approx.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in various genes encoding cardiac ion channels and membrane adaptor proteins are known to cause this syndrome [2], and many LQTS mutations have been identified [3][4][5][6]. A previous study [7] has shown that approx.…”
Section: Introductionmentioning
confidence: 99%
“…Compound mutations account for 4-8 % of the mutations identified in patients with LQTS, but the functional studies had only rarely performed. [10][11][12] The compound mutations may involve the same or different LQTS genes (e.g., two independent KCNQ1 mutations, KCNQ1 + KCNH mutations, KCNQ1 + SCN5A mutations, or rarely hERG + SCN5A mutations). [9][10][11][12] Functional hERG channels develop from the co-assembly of four subunits into a tetrametric protein on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Further diversity appears when an increasing number of compound heterozygote mutations within one or even two different LQTS genes have been reported. [9][10][11][12] Such compound mutations may increase the risk of arrhythmia and are associated with more severe forms of LQTS. But, to date, only limited studies have reported the functional alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Additional case reports showed that the clinical manifestations of patients with two concurrent mutations are often characterized by a more severe phenotype [12,13 ]. More recently it has become clear that LQTS patients carrying two or more pathogenic variants either in the same gene (compound heterozygotes) or in different genes (digenic heterozygosity), make up 4-9% of patients [9 ,14].…”
Section: The Additive Effect Of Multiple Mutationsmentioning
confidence: 99%